Komparasi sifat mekanik antara komposit epoksi berpenguat abu dan sekam padi - M. Martijanti; S. Sutarno; R. Sukwadi; M.B. Wahyu (Universitas Mataram, 2023)
Indonesia is an agricultural country because most of the population works in the agricultural sector. One of them is from agricultural products, namely rice. The milled rice produces rice and rice husks. Rice is used by the people of Indonesia as a staple food. Meanwhile, rice husks and ashes have not been utilized optimally. Seeing the great potential of rice husk and ash, efforts have been made to optimize the use of rice husk and ash as composite materials. The research aimed to obtain tensile strength, bending strength and porosity analysis of each composite using 230 mesh size rice husk particles or rice husk ash. The different volume fraction variations are 25% rice husk particles or its ashes and 75% epoxy matrix for the first variation, while for the second variation, it is 40% rice husk particles or its ashes and 55% epoxy matrix. The process of making composite materials was carried out using the hand lay-up and vacuum bag method with the test sample size according to the test standards used, namely ASTM D3039 for tensile strength testing and ASTM D790-61 for bending strength testing. The results of the mechanical properties test obtained the greatest tensile strength value in the epoxy composite reinforced with rice husk ash (40% wt) of 12.73 MPa and the greatest bending strength was in the epoxy composite reinforced with rice husk (40% wt) of 63.87 MPa. Preliminary characterization of rice husk and ash-reinforced epoxy composites met SNI standards.